2017
DOI: 10.4067/s0370-41062017000300011
|View full text |Cite
|
Sign up to set email alerts
|

Tetania severa por uso de enemas fosfatados, reporte de caso

Abstract: Background: Phosphate enemas are frequently used in the treatment of constipation. Errors in dosage and administration can lead to severe complications. Objective: To report a case of severe toxicity of phosphate enemas in a child with no risk factors. Case: 2 years old female, with functional constipation, was brought to emergency department because abdominal pain. She was diagnosed with fecal impaction and received half a bottle of Fleet Adult® (Laboratorio Synthon, Chile) two times, with no clinical resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Those at higher risk include patients with cardiac disease and reduced glomerular filtration rate (chronic or acute kidney diseases) [14]. A literature review showed that complications after enemas are also more common in children with gastroenterological conditions; for example, Hirschsprung's disease [17]. Yet, most of the reported severe adverse events were because of overdose, simultaneous admission of oral and rectal laxatives, or other contraindications [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those at higher risk include patients with cardiac disease and reduced glomerular filtration rate (chronic or acute kidney diseases) [14]. A literature review showed that complications after enemas are also more common in children with gastroenterological conditions; for example, Hirschsprung's disease [17]. Yet, most of the reported severe adverse events were because of overdose, simultaneous admission of oral and rectal laxatives, or other contraindications [18].…”
Section: Discussionmentioning
confidence: 99%
“…Núñez Sánchez reported a case of a generally healthy girl aged 2 years and 7 months, who had been given sodium-phosphate enema twice due to constipation. After 2 hours she presented painful hypertonia of the upper and lower extremities, and her laboratory tests showed hyperphosphataemia, hypocalcaemia, and metabolic acidosis [17].…”
Section: Discussionmentioning
confidence: 99%
“…6 Phosphate enema causes tetany due to hyperphosphatemia and subsequent development of hypocalcemia from metastatic calcium phosphate deposits. 63 Anecdotal case reports of tetany are seen with hyperemesis gravidarum, short bowel syndrome, Crohn's disease, and falciparum malaria. [64][65][66][67] Dengue fever may aggravate hypocalcemia of primary hypoparathyroidism and can present with tetany 5 .…”
Section: Approach To Tetanymentioning
confidence: 99%